Alternative tandem transcription initiation links noncoding variants to human disease through translational control - Zou, Xudong; Wang, Wei; Li, Xing; Wang, Yinuo; Chen, Hui; Chen, Shuxin; Weng, Feihong; Li, Qin; Yu, Chen; Li, Lei (浪淘沙预印本平台, 2025)
Alternative tandem transcription initiation (ATI) is a pervasive mechanism of gene regulation, yet its genetic impact on human disease remains largely unknown. Here, we systematically quantified genetic regulation of ATI across 25,859 samples from 49 human normal tissues and 33 tumor tissues. We identified ~0.4 million 5′ UTR ATI quantitative trait loci (5′aQTLs) in 5,295 genes, with 32% operating independently of gene expression. Moreover, we discovered 2,238 multi-tissue ATI outliers enriched for rare deleterious promoter and 5′ UTR variants, demonstrating that both common and rare variants modulate transcription initiation. Strikingly, 74% of disease variants that colocalize with 5′aQTLs cannot be identified by eQTLs. Transcriptome-wide association studies identified 614 ATI-mediated disease susceptibility genes, including known cancer drivers such as MAFF and MLLT10. Functional validation uncovered OSGEP as a novel breast cancer risk gene, where the alternative allele lengthens the 5′ UTR and reduces protein abundance through upstream open reading frame (uORF)-mediated translation repression, and suppresses breast cancer cell proliferation. Our findings establish ATI as a major, underappreciated mechanism linking noncoding variation to disease, providing a critical resource for interpreting disease risk loci.